Poesía moderna : reunión - Bonifaz Nuño, Rubén (autor) ((Material de Lectura. Poesía Moderna ;, 1977)
Contiene poemas de Rubén Bonifaz Nuño, Isabel Fraire, Jaime García Terrés, Ulalume González de León, Hugo Gutiérrez Vega, Efraín Huerta, Eduardo Lizalde, Marco Antonio Montes de Oca, José Emilio Pacheco, Octavio Paz, Tomás Segovia y Gabriel Zaid.